The phylogeny of the four pan-American MtDNA haplogroups: Implications for evolutionary and disease studies - Achilli, Alessandro (2008)
Only a limited number of complete mitochondrial genome sequences belonging to Native American haplogroups were available until recently, which left America as the continent with the least of information about sequence variation of entire mitochondrial DNAs. In this study, a comprehensive overview of all available complete mitochondrial DNA (mtDNA) genomes of the four pan-American haplogroups A2, B2, C1, and D1 is provided by revising the information scattered throughout GenBank and the literature, and adding 14 novel mtDNA sequences. The phylogenies of haplogroups A2, B2, C1, and D1 reveal a large number of sub haplogroups but suggest that the ancestral Beringian population(s) contributed only six (successful) founder haplotypes to these haplogroups. The derived are overall starlike with coalescence times ranging from 18,000 to 21,000 years (with one exception) using the conventional calibration. The average of about 19,000 years somewhat contrast with the corresponding lower age of about 13,500 years that was recently proposed by employing a different calibration and estimation approach. Our estimate indicates a human entry and spread of the pan-American haplogroups into the Americas right after the peak of the Last Glacial Maximum and comfortably agrees with the undisputed ages of the earliest Paleoindians in South America. In addition, the phylogenetic approach also indicates that the pathogenic status proposed for various mtDNA mutations, which actually define branches of Native American haplogroups, was based on insufficient grounds.